IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP PEREMPUAN SEBAGAI KORBAN TINDAK PIDANA PELECEHAN SEKSUAL DALAM TRANSPORTASI - Sri Wahyuni Laia (LPPM Universitas Nias Raya, 2023)
Legal protection is used to protect victims, and guarantee their rights and obligations to the criminal justice system and the current sentencing system. Especially for those seeking the truth who have been sexually harassed. The author found several forms of criminal acts of sexual harassment that occurred on online transportation from 2015 to the present. In this case, the issues raised by the author regarding the criminal forms of sexual harassment on online transportation, as well as knowing how the legal protection is. The method carried out by the author in this study is to use normative research methods. Where the author uses primary legal sources, secondary legal materials and related tertiary legal materials to obtain sources of material regarding the forms of criminal acts of sexual harassment on online transportation and legal protection according to its legislation. Based on the results of this study, from 2016 to 2018 there were 7 criminal cases of sexual harassment that occurred on online transportation. To avoid this from repeating itself, the government and companies that house online transportation must work together to protect consumers and drivers themselves by ratifying the Minister of Transportation Regulation Number 108 of 2017 and adding an SOS button or panic button listed on the application. The conclusion of this study is that legal protection of women as a criminal act of online transportation has been carried out as it should be along with the times.